The Influence of School Leadership Style and Student Learning Outcomes on Teacher Performance At State Basic Schools in Air Kumbang Sub-District - Romli; Harapan, Edi; Wardiah, Dessy (Jurnal Pendidikan Tambusai, 2021)
This study aims to determine and describe the influence of the principal's leadership style and student learning outcomes motivation on teacher performance. With quantitative research methods. The method used is descriptive quantitative method used to process data characteristics related to the average number, look for percentages, and present interesting, easy-to-read data. Data in the form of a questionnaire is classified as quantitative data. The technique of collecting data in this research is through a questionnaire. The results showed that; (1) These findings provide evidence that an increase in the leadership style of a principal by a headmaster will have an impact on improving the performance of public elementary school teachers in Air Kumbang District. (2) there is an influence between the motivation of student learning outcomes on teacher performance. These findings provide evidence that increased motivation for learning outcomes will have an impact on improving the performance of SD Negeri teachers in Air Kumbang District. (3) there is an influence between the principal's leadership style and the motivation of student learning outcomes simultaneously on teacher performance. These findings provide evidence that increasing the principal's leadership style and motivation for learning outcomes will have an impact on improving the performance of SD Negeri teachers in Air Kumbang District.